MENTAL HEALTH ISSUES AND HELP-SEEKING BEHAVIOUR AMONG MALAYSIAN ACADEMICS: A PRELIMINARY STUDY (Jurnal Pembangunan Sosial, 2022)
The National Health and Morbidity Survey (NHMS) reported the number of mental health cases among Malaysian aged 16 years andabove has shown an increment trend - 10.7% (1996), 11.2% (2006) and 29.2% (2015). In the year 2015 only, 1 in 3 Malaysians havemental health problems. NHMS report in 2019 showed that the occurrence of depression among Malaysian adults is about half amillion people. These statistics obviously hinted that something is missing when dealing with mental health issues in Malaysia. Thoughmany studies have been conducted in the past, most are focusing on the causes, and little attention has been given on the aspect of helpseeking in addressing mental health issues. Therefore, this study was done to explore factors that influence individuals to seek help when having mental health problem. To uncover these issues, input from 3 participants were gathered through an online semi-structured interview. Through snowball sampling technique, the participants were invited and willingly to participate in this study. Specifically, 2 participants are the academics from private universities in Malaysia and 1 participant is an academic from a public university in Malaysia. As shared by the participants, the main factor that forces them to seek help is due to not able cope with the problems any longer. On the other hand, stigma from the society, job insecurity, and lack of management support and preservation of profession credibility were found to be among the factors that hinder a person to go and seek helps. Based on the findings, several suggestions and recommendations were put forward to encourage more people to go and seek professional help.